Influence of mate and nest-site fidelity on a declining, urban avian population - Lynne A. Trulio; Debra A. Chromczak; Philip G. Higgins (PLoS ONE, 2025)
As urbanization reduces species’ habitats and population sizes, managers need information on whether within-population processes, such as changes in mate and nest-site fidelity and dispersal distances, may be contributing to declines. Few avian studies have examined changes in these behaviors in declining populations or in urban settings. We investigated whether mate fidelity, nest-site fidelity or breeding dispersal distance changed over time in a population of burrowing owls (Athene cunicularia), a short-lived, socially-monogamous species. During the 18-year period of the study, the population declined by 69% in urban Santa Clara County, California, USA--a region of rapid urbanization. We assessed whether these behaviors were influenced by key factors including age, breeding success in the previous year, and years with the same mate, and examined the relationship between mate and nest-site fidelity over time and annual reproductive success. Our analyses showed no change over time in mate fidelity rates, nest-site fidelity rates, dispersal distances or annual reproductive success, indicating these behaviors remained stable even during a severe population decline. Although burrowing owls are a short-lived species, we found that increasing years with the same mate resulted in increased nest-site fidelity and annual reproductive success. To achieve increasing annual reproductive success in this species and others with similar fidelity behaviors, nest sites and pairs must be protected over many years allowing mates to stay together in the same nest territory. Since these fidelity behaviors were maintained during the population decline, other factors require investigation to determine the causes for decreases in this population. Burrowing owls are an urban-adaptable species that can maintain important fidelity behaviors in human-altered habitats. However, even such species are subject to population declines in urban settings.